Cidades inteligentes e Ciência da Informação - Caldas, Rosângela Formentini (Editora Oficina Universitária, 2021)
The book Smart Cities & Information Science brings together leading specialists and researchers in the field of Information Science, with the aim of bringing the areas closer together. Through a dialogue with the most prominent themes in the context of smart cities today, we invite readers to explore the understanding and possibilities of the challenges that arise for this subject. Smart Cities are places recognized for the practice of innovation and knowledge, providing a diversity of effective tools for urban growth, establishing spaces for generating improvements in the population's quality of life. With the aim of contributing to the possibilities that open up for new practices in strategic topics of Regional Public Management, Sociocultural Factors and Cultural Units/Informational Institutions, we hope to open up reflection on the need to approach areas that produce such significant content and that could centralize their research for the growth and development of the regions.